Acceptability of reducing sedentariness using a mobile-phone application based on 'if then' plans for people with psychosis: A focus-group study conducted in North West England, UK. (August 2022) - Bailey, Rachel; Bartlett, Y Kiera; Hassan, Lamiece; Armitage, Christopher J; Stockton-Powdrell, Charlotte; Machin, Matthew; Lewis, Shon; Epton, Tracy
Objective: To understand the acceptability of (a) reducing sedentary-behaviour in people with psychosis using 'if-then' plans and (b) the proposed app content. Design: Qualitative acceptability study. Method: Three structured focus-groups and an interview were conducted with eight participants who had experience of a psychotic episode. They discussed sedentary-behaviour, being more active, critical situations in which they may be tempted to be sedentary and solutions to these (the if-then plans), and a mock-up of the mobile application. The Theoretical Framework of Acceptability (TFA) was used to analyse qualitatively the transcripts. Results: All TFA constructs were coded in each of the transcripts. The idea of reducing sedentary-behaviour was acceptable to people with psychosis, participants knew the importance of being more active, however it is not always their main priority. Likewise, the proposed content of the app was found to be acceptable, with participants already using some of the proposed solutions. Conclusion: This was the first study to use the TFA framework to assess the acceptability of an app that uses critical situations and solutions ('if-then plans') to help reduce sedentary behaviour for people with psychosis. In this sample (male, English speaking mainly white people), participants understood the benefits of being more active. However, reducing sedentary-behaviour is not the main priority of this population and being sedentary has benefits when their mental-health is bad.